Effects of day and night on swimming, grazing and social behaviours of rohu Labeo rohita (Hamilton) and common carp Cyprinus carpio (L.) in simulated ponds - Rahman, Mohammad Mustafizur; Verdegem, Marc; Wahab, Md Abdul; Hossain, Md. Yeamin; Jo, Qtae (Wiley-Blackwell, 2008)
Diel rhythmicity of grazing, swimming, resting and social interactions of rohu (Labeo rohita) (weight 66.5-68.3 g) and common carp (Cyprinus carpio) (79.9^82.0 g) were observed in 1m2 simulated ponds using video images. Fish behaviour was monitored during a full 24-h period, starting at 08:00 hourswith a15-min recording, which was repeated every 3 h. Rohu spent more time grazing during the day than at night. Grazing activity peaked at the beginning and at the end of the day. Grazing and resting of rohu were negatively correlated. Common carp grazed day and night, showing no distinct grazing peak. Considering the grazing time of rohu and common carp, a feeding schedule with two feeding times at 07:30 and16:30 hours might be appropriate for better food intake and conversion in rohu-common carp polyculture system.